The Effect of Heat Treatment on the Tribological Properties and Room Temperature Corrosion Behavior of Fe-Cr-Al-Based OPH Alloy - Khalaj, Omid; Saebnoori, Ehsan; Jirková, Hana; Chocholatý, Ondřej; Kučerová, Ludmila; Hajšman, Jan; Svoboda, Jiří (Materials (Basel, Switzerland), 2020)
The microstructure, mechanical, tribological, and corrosion properties of Fe-Cr-Al-Y-based oxide-precipitation-hardened (OPH) alloy at room temperature are presented. Two OPH alloys with a composition of 0.72Fe-0.15Cr-0.06Al-0.03Mo-0.01Ta-0.02Y2O3 and 0.03Y2O3 (wt.%) were prepared by mechanical alloying with different milling times. After consolidation by hot rolling, the alloys presented a very fine microstructure with a grain size of approximately 180 nm. Such a structure is relatively brittle, and its mechanical properties are enhanced by heat treatment. Annealing was performed at three temperatures (1000 °C, 1100 °C, and 1200 °C), with a holding time from 1 to 20 h. Tensile testing, wear testing, and corrosion testing were performed to evaluate the effect of heat treatment on the behavior and microstructural properties. The grain size increased almost 10 times by heat treatment, which influenced the mechanical properties. The ultimate tensile strength increased up to 300% more compared to the initial state. On the other hand, heat treatment has a negative effect on corrosion and wear resistance.
Keywords: corrosion; heat treatment; oxide precipitation hardened (OPH); wearing; tribology; Fe–Cr–Al